Respons Pelajar Institut Pengajian Tinggi Awam Terhadap Pluraliti Agama di Malaysia: Response among the Students of the Public Higher Learning Institution towards Religious Plurality in Malaysia - Mohd Sharif, Mohd Farid; Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
This study was aimed to analyse the response among the students of the Public Higher Learning Institution (IPTA) towards religious plurality in the context of pluralist society in Malaysia. The study involved 800 respondents selected from four IPTAs. The data of the study collected through questionnaire and analysed by SPSS programme. Descriptive statistic through frequency, percentage, min, crosstabulation and correlation coefficient were applied in this study to explain the respondent’s background and the student’s response towards religious plurality. The findings showed that the reception of the students towards religious plurality were reasonably bad, i.e., every religion is true, every individual must know other religion principles as precondition for making pluralist society, religious freedom is a right for everyone. The findings also indicated that the religion factor and the types of education of primary and secondary school were enormously influential over the student’s response towards religious plurality.